A Conceptual Paper on the Effects of Green Intellectual Capital on Business Sustainability - Sauid, Muna Kameelah; Hasan, Zuhairah; Sauid, Zulaika (Information Management and Business Review, 2023)
Businesses today are placing greater emphasis on sustainability and environmental concerns. More and more firms are making sustainability their top priority to stay ahead of their competitors. Since we now operate in a knowledge-based economy, intangible assets have emerged as an essential measure for evaluating a company’s competitive advantage. Academics developed the notion of green intellectual capital (GIC) to encourage firms to care more about their environmental impact. In this conceptual paper, we aim to investigate the relationship between Green Intellectual Capital and the sustainability of a business. The goal of this study was to present a literature review on the impact of Green Human Capital (GHC), Green Structural Capital (GSC), and Green Relational Capital (GRC) on business sustainability. Despite the growing importance of GIC research in developing countries, scholars have devoted little attention to the subject, particularly in the Malaysian context. The findings indicate that all three concepts of Green Intellectual capital positively influence the sustainability performance of businesses.